Metacognitive Capacity Is Related to Self-Reported Social Functioning and May Moderate the Effects of Symptoms on Interpersonal Behavior. Issue 2 (February 2020) - Fischer, Melanie W.; Dimaggio, Giancarlo; Hochheiser, Jesse; Vohs, Jenifer L.; Phalen, Peter; Lysaker, Paul H.
Abstract : Abstract: Impairments in metacognition or the ability to form integrated senses of self and others have been linked to deficits in laboratory-based measures of social functioning in schizophrenia. This study examined whether self-reported social functioning was related to metacognition in 88 adults in a nonacute phase of schizophrenia. Concurrent assessments were made of metacognition with the Metacognition Assessment Scale–Abbreviated, social functioning with the Social Functioning Scale, symptoms with the Positive and Negative Syndrome Scale, and neurocognition with the Wisconsin Card Sorting Task. Univariate correlations revealed that self-reported social functioning was related to metacognition. Symptom severity was linked to interpersonal relationships, and overall metacognition was found to significantly moderate that relationship such that the effects of symptoms on function grew less as metacognitive capacity was stronger, independent of the effects of neurocognition. This may suggest the potential of metacognitive interventions to titrate the negative effects of symptoms on social function.